2022
DOI: 10.1088/1755-1315/1039/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic Factors Affecting Food Security for Low-Income Household During the COVID-19 Pandemic in the Special Region of Yogyakarta

Abstract: The COVID-19 pandemic has affected household food security, especially those with low incomes. This study aims to: (1) analyze the influence of socio-demographic factors (gender, age, mother’s education, marital status, occupation, dependents, income, and social assistance) on food security. (2) Measuring the level of food security of low-income families in the Special Region of Yogyakarta seen from the share of food expenditure, using a cross-sectional design and a quantitative approach and involved a sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The results indicated that more than half of the total households had food insecurity, with the most significant proportion being severe. This finding aligns with similar studies on COVID-19 (Hermawati et al, 2022;Syafiq et al, 2022;Dewi et al, 2023). COVID-19 has significantly impacted family incomes, as demonstrated by the marked disparity in family income and food security.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results indicated that more than half of the total households had food insecurity, with the most significant proportion being severe. This finding aligns with similar studies on COVID-19 (Hermawati et al, 2022;Syafiq et al, 2022;Dewi et al, 2023). COVID-19 has significantly impacted family incomes, as demonstrated by the marked disparity in family income and food security.…”
Section: Discussionsupporting
confidence: 91%
“…The determinants of food security in Tulungagung include income, employment status, and type of social assistance, as noted by Dewi et al (2023). Similarly, Hermawati et al (2022) found that factors influencing food security in Yogyakarta were employment status, family income, and number of dependents. Engel's law states that increased income directly leads to increased food consumption.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Three sociodemographic factors affect food security, these are employment, income and the number of dependents (Ashari et al, 2022). The pandemic has also exacerbated the conditions of poverty for the community of Yogyakarta (Hermawati et al, 2022). Other study found that being a female, unemployed and living in Java are the low factors associated with food security, while have a history of stress or depression, poor dietary habits and living alone are the strong factors (Ashari et al, 2022).…”
Section: The Covid-19 Pandemic Affected Household Food Securitymentioning
confidence: 99%
“…Food insecurity was affected by many factors. The most studies conducted found that the gender of household heads (Andani & Adi, 2021;Ashari et al, 2022;Manyullei & Arundhana, 2021;Purnasari et al, 2020), age of household heads (Andani & Adi, 2021;Hermawati et al, 2022;Iguna et al, 2022), family size (Ashari et al, 2022;Syafiq et al, 2022), uncoupled households (Ashari et al, 2022), marital status of the head of household (Iguna et al, 2022;Sitompul et al, 2023), educational level of women handling food, educational status of household head (Manyullei & Arundhana, 2021;Primaningrum et al, 2022) and economic status were determining factors of food insecurity (Iguna et al, 2022;Syafiq et al, 2022). The Food and Agriculture Organization (FAO) has warned that the pandemic of Covid-19 would affect the food security of many countries, especially poor and developing countries.…”
Section: Introductionmentioning
confidence: 99%